Morphometric and morphological analysis of neuromuscular junction alterations in the denervated rat diaphragm - Torrejais, M. M.; Soares, J. C. [UNESP]; Matheus, S. M. M. [UNESP]; Mello, J. M.; Francia-Farje, L. A. D. [UNESP]; Vicente, E. J. D. (Soc Chilena Anatomia, 2009)
The morphological and structural alterations that occur in the neuromuscular junctions of the denervated rat diaphragm were studied. Fifteen adult male albino rats (Rattus norvegicus) aged about 60 days and with a mean weight of 200 g were used. Chronically denervated diaphragms were obtained and the animals were sacrificed after 4, 8 and 12 weeks of denervation. The left antimere of the diaphragm was denervated by section of the phrenic nerve and the right antimere was used as control. Each antimere was divided into three fragments: one was used for histochemical (nonspecific esterase) and morphometric study of neuromuscular junctions, and the other two were used for transmission and scanning electron microscopy (SEM) analysis. Histochemical analysis of the diaphragm neuromuscular junctions after denervation showed only small changes in junction morphology. However, these junctions became smaller and elongated and presented less visible contours with increasing time of denervation. Ultrastructural analysis of neuromuscular junctions after 12 weeks showed more or less organized junctional folds on the muscle fiber surface. The junctional cytoplasm exhibited important alterations such as mitochondrial degeneration and the presence of numerous filaments. SEM revealed the presence of deep primary synaptic grooves with peripheral excavations which housed the nerve terminal boutons and exhibited internally the secondary synaptic clefts present among the junctional folds of the sarcolemma. This study showed that some of the morphological changes demonstrated in other denervated striated skeletal muscles are not repeated at the same intensity or in the same temporal pattern in the rat diaphragm.

En este trabajo se estudiaron las alteraciones morfológicas y estructurales de las uniones neuromusculares en el diafragma denervado de ratas. Se utilizaron 15 ratas albinas (Rattus norvegicus), machos, adultos, con peso promedio de 200g y cerca de 60 días de edad. Los diafragmas crónicamente denervados fueron obtenidos y los animales se sacrificaron después de 4, 8 y 12 semanas de denervación. El antímero izquierdo del diafragma fue denervado por sección del nervio frénico y el antímero derecho fue utilizado como control. Cada antímero fue dividido en 3 fragmentos: uno fue utilizado para el estudio histoquímico (esterasa inespecífica) y morfométrico. Los otros dos se destinaron al estudio de microscopía electrónica de transmisión (MET) y microscopia electrónica de barrido (MEB) de las uniones neuromusculares. El estudio histoquímico de las uniones neuromusculares posterior a la denervación, muestra que la morfología de esas uniones sufre pequeñas alteraciones. Con la evolución del tiempo de denervación esas uniones muestran tamaños menores, son alargadas y con contornos menos nítidos. La ultra-estructura de las uniones neuromusculares después de 12 semanas, demostró que la superficie de la fibra muscular exhibe pliegues de unión más o menos organizados. La región del citoplasma de unión exhibe alteraciones importantes, con degeneración mitocondrial y presencia de muchos filamentos. En MEB se observa que los botones sinápticos primarios son profundos, presentan escavaciones periféricas donde estaban alojados los botones de las terminaciones nerviosas y exhiben internamente, los espacios sinápticos secundarios presentes entre los pliegues de unión del sarcolema. Este estudio mostró que algunos patrones morfológicos demostrados en otros músculos estriados esqueléticos denervados no se repiten con la misma intensidad y curso temporal en el diafragma de ratas.
Evaluación de las alteraciones morfológicas y morfométricas de las uniones neuromusculares del diafragma denervado en ratas.
Keywords: Diaphragm; Neuromuscular junction; Denervation; Rat